Market Specific News and Its Impact on Electricity Prices: Forward Premia - Ewa Lazarczyk (Research Institute of Industrial Economics (IFN), 2013)
This paper studies the impact of market specific news on the short-time forward premia on the Scandinavian electricity market. I show that the short time premia between the day-ahead and intra-day electricity prices on the Scandinavian market can be explained by the arrival of news specific to the power market. By exploring the types of news I indicate that production failures shape the premia. Production disruptions in coal-powered units are most frequent and have the greatest effect on the differences between the day-ahead and intra-day prices.
Keywords: D40; G14; L94; Q40; 330; Intra-day electricity market; Forward premia; Market specific news; Supply shocks